2018
DOI: 10.1053/j.ajkd.2018.02.353
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Telehealth Interventions on Processes and Quality of Care for Patients With ESRD

Abstract: Caring for patients with end-stage renal disease (ESRD) requiring dialysis is intensive and expensive. Telehealth may improve the access and efficiency of ESRD care. For this perspective, we systematically reviewed studies that examined the effectiveness of telehealth versus or in addition to usual care for ESRD management. 10 studies were identified, including 7 randomized trials and 3 cohort studies. Study populations, modes of delivery (including telephone, telemetry, or videoconferencing), and the outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 26 publications
(87 reference statements)
1
42
0
2
Order By: Relevance
“…There have been two recent reviews which have explored the use of eHealth intervention within CKD more broadly. 43,44 Compared with these previous reviews, this study has included more studies (15 studies, in contrast to 4 studies 43 and 6 studies 44 ) and examined additional outcomes specific to PD patients. Nonetheless all the reviews conducted to date, including this one, have not identified any adverse effects associated with the use of eHealth interventions for patients on PD.…”
Section: Discussionmentioning
confidence: 99%
“…There have been two recent reviews which have explored the use of eHealth intervention within CKD more broadly. 43,44 Compared with these previous reviews, this study has included more studies (15 studies, in contrast to 4 studies 43 and 6 studies 44 ) and examined additional outcomes specific to PD patients. Nonetheless all the reviews conducted to date, including this one, have not identified any adverse effects associated with the use of eHealth interventions for patients on PD.…”
Section: Discussionmentioning
confidence: 99%
“…Specialties with evidence demonstrating telehealth effectiveness include oncology, diabetology (including diabetes education services), cardiology, nephrology, psychiatry and addiction services, primary care, geriatrics, and women’s health. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 For instance, DeNicola et al’s systematic review 17 of telehealth interventions in women’s services found improvements in rates of perinatal smoking cessation, breastfeeding and scheduling of office visits, and obstetric outcomes. For the common chronic disease state of obesity, Huang et al’s systematic review 18 found telemedicine visits to be an effective intervention in reducing body weight for patients with or without hypertension and diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Outcomes associated with PD include increased satisfaction [13], increased quality of life [15,16], and survival advantage, especially in the first few years of therapy [17-19], with decreased costs to the health care system [20]. Virtual care, often referred to as telehealth or telemedicine, is a rapidly evolving area where health care services are delivered, in part, through technology, including clinician-to-clinician, clinician-to-patient, and patient-to-mobile health technology communication that aims to enhance patients’ self-management of their disease in a home setting [4,17,20,21]. Technology includes remote monitoring [4,21,22], mobile phones [5,23], virtual wards [24], and Web-based eHealth portals [25].…”
Section: Introductionmentioning
confidence: 99%
“…Virtual care, often referred to as telehealth or telemedicine, is a rapidly evolving area where health care services are delivered, in part, through technology, including clinician-to-clinician, clinician-to-patient, and patient-to-mobile health technology communication that aims to enhance patients’ self-management of their disease in a home setting [4,17,20,21]. Technology includes remote monitoring [4,21,22], mobile phones [5,23], virtual wards [24], and Web-based eHealth portals [25]. Virtual care, coupled with PD, has the potential to improve access for CKD care for patients in their own homes [26-30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation